2002
DOI: 10.1007/pl00012500
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugates of the intestinal goblet cells of four cyprinids

Abstract: The aim of this work was to show differences in the terminal and subterminal sugar composition of carbohydrate chains of glycoconjugates produced by the goblet cells of the intestines of four cyprinids. We analysed intestines of two herbivorous species--sneep and grass carp--and two omnivorous ones--chub and common carp. We compared four intestinal regions of every studied species. In every region, the presence of neutral and acidic glycoconjugates was confirmed. The smallest amount of acidic glycoconjugates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 30 publications
3
50
2
2
Order By: Relevance
“…Therefore, biochemical methods seem to be more suitable for the characterization of intestinal glycoproteins than histochemical techniques. In agreement with the findings of Fiertak & Kilarski (2002), our study of carp mucus demonstrated (in general) no fucose, but large amounts of N-acetyl-α-galactosamine and N-acetyl-β-galactosamine (via DBA and RCA) as main terminal residues. However, by Day 3 after the stimulus, a faint positive lectin reaction for fucose was measured.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, biochemical methods seem to be more suitable for the characterization of intestinal glycoproteins than histochemical techniques. In agreement with the findings of Fiertak & Kilarski (2002), our study of carp mucus demonstrated (in general) no fucose, but large amounts of N-acetyl-α-galactosamine and N-acetyl-β-galactosamine (via DBA and RCA) as main terminal residues. However, by Day 3 after the stimulus, a faint positive lectin reaction for fucose was measured.…”
Section: Discussionsupporting
confidence: 91%
“…In turbot, neutral mucins also dominate in the digestive tract and acidic mucins are not present (Redondo & Alvarez-Pellitero 2010a). The most common observation is that acidic and neutral mucins dominate and few acid mucopolysaccharides possess sulphate groups, while the majority are carboxylic, as in the current study (Scocco et al 1997, Domeneghini et al 1998, 2005, Fiertak & Kilarski 2002, Park et al 2003, Leknes 2010. The coexistence of neutral and acid glycoconjugates probably reflects different ages or stages of differentiation for GC (Elbal & Agulleiro 1986, Murray et al 1996, Leknes 2010.…”
Section: Discussionsupporting
confidence: 49%
“…Feeding habits seem to be correlated with the pattern of glycoconjugate glycosylation in different cyprinid fish (Fiertak & Kilarski 2002). However, there is almost no information on the specific effect of diet composition on mucin pattern in the intestine of fish, and most studies are focused on the effects on intestine morphometry (Escaffre et al 2007), intestinal fatty acid uptake (Geurden et al 2009) and digestive enzymes (Santigosa et al 2008, Silva et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that mucus containing glycoproteins rich in anions, i.e. acidic mucus, has a markedly higher viscosity than neutral mucus (Tibbetts 1997;Domeneghini et al 1999;Fiertak and Kilarski 2002). Generally, mucus rich in sulphated glycoproteins is regarded to have the highest viscosity of all types of mucus (Sibbing and Uribe 1985).…”
Section: Discussionmentioning
confidence: 98%